IDENTIFIKASI PELUANG PEMILIHAN FASILITAS PARK AND RIDE PADA STASIUN MRT JAKARTA - Ayudia, Saila
Congestion in DKI Jakarta is a phenomenon that is commonly felt everyday by all motorists. Under these conditions, there needs to be a change in approach in transportation planning, that is, from the development of the supply side to the demand side or commonly referred as Transportation Demand Management (TDM). One of the strategy of transport demand management is to shift the use of transportation modes by optimizing the role of mass public transportation. Reducing the use of private vehicles can be done by increasing public interest in the use of public transportation for daily commuting activities. In addition to improving the quality of public transport facilities and services themselves, providing parking at public transportation stops is believed to be able to attract private vehicle users to switch modes. The provision of park and ride facilities is considered effective in encouraging public interest to transit and then switching to public transportation. The park and ride concept has been applied to several of MRT Jakarta stations, such as Lebak Bulus Grab Station and Fatmawati Station. But unfortunately, those park and ride facilities have not been fully utilized by private vehicle users. This can be caused by several factors. Based on these matters, a study should be conducted aimed at identifying the opportunities for park and ride facility selection at the MRT Jakarta station. The findings of the study conclude that factors that influence the preferences of DKI Jakarta commuters who have private vehicles to be willing to use MRT Jakarta as a commuting mode with park and ride facilities include factors such as the easeness of accessibility, service, and use of facilities provided, such as the easeness of access MRT station and park and ride facilities, easeness to get parking, and easeness to pay on MRT and park and ride facilities. Other than that, the absence of park and ride facilities at the nearest MRT station from potential users is an important factor in the selection of park and ride facility at the MRT Jakarta station.